PHOTOGRAPHY BEHAVIOR AND MOTIVATION FACTORS : A STUDY OF CHINESE TOURISTS TO THAILAND - KEYU, DENG; THALDUMRONG, PAK (Chinese Language and Culture Journal, 2016)
Tourism and photography are closely linked. Through photography, traveling experiences can be recorded, and tourist destination can be established and promoted. Therefore, photographing behavior has both meaningful symbol and research value. Chinese are the largest number of tourists to Thailand. In relation to that development, photograph images containing Thai elements are very popular in China recently. More and more Chinese tourists are now visiting Thailand. Therefore, their photographing motivation factors are worthwhile to investigate. Research model of the study was developed following literature review. The researcher proposed that photographing motivation factors are proof of visit; record of special moment; beauty of scenery; self-expression; memory, data collection; and tools to draw attention on social media. The study is a quantitative research employing questionnaires survey. Data were analyzed using SPSS. The study reveals that beauty of scenery is the most influencing motivation factor, and there are different degrees of correlation between motivation factors and tourist photographing behavior. Certain behavior may be associated with more than one motivation factor; on the other hand a motivation factor may produce various behaviors. The study summarizes Chinese tourist photographing behavior covering the combination of both photographing and tourist experience. Recommendations are given to related industries and tourism sector to help them understand better the value of travel photography.